(untitled) (Research, Society and Development, 2022)
The objective was to carry out the analysis of the slaughter of cattle as a component of surveillance for foot-and-mouth (FMD) disease in the state of Maranhão, in the year 2020. For this purpose, a descriptive epidemiological study was carried out using secondary data extracted from: i) Animal Transit Guide (ATG) for the slaughter of cattle issued in the year 2020; ii) list of slaughterhouses; and iii) a report on the registration of the points of greatest risk for the spread of diseases. Additional data on slaughter convictions in establishments registered in the Federal Inspection Service were extracted from the website of the Ministry of Agriculture, Livestock and Supply. The following effectiveness indicators were obtained: i) distribution of establishments that slaughter species susceptible to foot-and-mouth disease; ii) distribution and concentration of animal origin; iii) percentage of animals and properties that sent animals susceptible to FMD for slaughter; and iv) number of investigations with probable cases from this surveillance. The results showed that 38,612 (97.488%) ATG were issued, with 37,642 (96.226%) cattle. Of these movements, 93.05% were destined for within the state (slaughter within the municipality of origin of the animals). The movement for slaughter accounted for 9,015 (8.53%) of the registered properties. It is concluded that the bovine species is, among the species susceptible to foot-and-mouth disease, the one with greater prominence for the purpose of slaughter and for supplying the internal consumer market of Maranhão, with the West region being the most expressive in the number of ATG emissions and number of cattle for this purpose.